2009
DOI: 10.1007/s10623-009-9312-0
|View full text |Cite
|
Sign up to set email alerts
|

Equidistant frequency permutation arrays and related constant composition codes

Abstract: In this paper we study the special class of equidistant constant composition codes of type CCC(n, d, µ m ) (where n = mµ), which correspond to equidistant frequency permutation arrays; we also consider related codes with composition "close to" µ m . We establish various properties of these objects and give constructions for optimal families of codes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…The construction of 2DMCWC(nl, n, d, 1, l)s has been investigated in many papers as equidistant frequency permutation arrays and constant-composition codes [27], [28]. Most of the constructions can be generalized to construct 2DMCWC(m, n, d, w, l).…”
Section: B Constructionsmentioning
confidence: 99%
“…The construction of 2DMCWC(nl, n, d, 1, l)s has been investigated in many papers as equidistant frequency permutation arrays and constant-composition codes [27], [28]. Most of the constructions can be generalized to construct 2DMCWC(m, n, d, w, l).…”
Section: B Constructionsmentioning
confidence: 99%
“…Permutation code [16] (q(q + 1), q 2 ) q for prime powers q q 2 q 0 Frequency permutation array [12] ( q(kq [18] (2q − 1, 2q In particular, only six infinite nontrivial families of optimal codes with n > q are known. However, code parameters for these six families are such that their relative narrowband noise error-correcting capability to length ratios diminish to zero as q grows.…”
Section: Theorem 23 the Following Holds (I)mentioning
confidence: 99%
“…Details are provided in Table II. We then prove the lemma by induction on m ≥ 97. Let E = {t : t ≥ 9} \ {10, 14,15,18,20,22,26,30,34,38, 46, 60}. By Theorem 4.8, a TD(7, n) exists for any n ∈ E. If there exists a special GBTD 1 (3, m ) for odd m , 7 ≤ m ≤ 2n + 1, then apply Lemma 7.2 with 3 ≤ g 1 , g 2 ≤ n to obtain a special GBTD 1 (3, m) for odd m, 10n + 7 ≤ m ≤ 14n + 1.…”
Section: Existence Of Gbtd 1 (3 M)mentioning
confidence: 99%
See 1 more Smart Citation
“…Vinck [31] studied this channel and showed that -ary frequency shift keying ( -FSK) modulation, in conjunction with the use of permutation codes, provides a constant power envelope, frequency spreading, and redundancy to correct errors resulting from the harsh noise pattern. This has since resulted in research on frequency permutation arrays (FPAs) and constant composition codes (CCCs) which retain the property of a constant power envelope (see [5]- [16], and [14] for a survey). Every codeword of an FPA or a CCC has the requirement that the frequency of each symbol is fixed by the parameters of the code.…”
Section: Introductionmentioning
confidence: 99%